Analysis of Three-Wheeler Vehicle Structure at the Event of Side Pole Crash - Daniel Hambissa; Ramesh Babu Nallamothu; Tigist Andarge (Journal of Engineering)
This work reports on the simulation of three-wheel vehicles in the event of a side pole crash. In this study, the dynamic characteristics of the three-wheeler vehicle during pole collision were studied using finite elements. The TWV model used here was created using CATIA v5 and simulated using LS-DYNA which is widely used by the automotive industry to analyze vehicle design and predict a car’s behavior in a collision. Moreover, in this study, the finite element model of the side hybrid 5th percentile male dummy was developed for studying the driver and occupant responses in crash events of side pole. Based on the analysis results obtained from the existing model of TWV, modifications were made on the side structure by means of adding energy-absorbing components. Then, the modified TWV was analyzed under the same condition as the existing one. The result of the simulations shows that with the modification, 80 mm more living space, 630 N reduction of impact force, and 0.8 kJ of additional absorbed energy were obtained. So with the modified model, the safety and crashworthiness of the TWV were greatly improved during side collision without affecting the appearance and weight of the existing models.